Endoscopic Removal Through a Gastrostomy of Swallowed Acupuncture Needles - Yeo Wool Kang; Dong Kyun Kim (The Korean Journal of Gastroenterology, 2021)
Acupuncture is a representative treatment field in oriental medicine that is used widely in various medical conditions. Although acupuncture is considered a safe procedure, it can cause complications. This paper reports the case of a 44-year-old quadriplegic woman who received a percutaneous gastrostomy (PEG) tube and was referred for the endoscopic removal of swallowed acupuncture needles. The needles were removed successfully by endoscopy through the PEG tube using the rendezvous technique without significant complications.